Building Web and Mobile ArcGIS Server Applications with JavaScript - Pimpler, Eric (Packt Publishing, 2017)
Master the ArcGIS API for JavaScript to build web and mobile applications using this practical guide. About This Book Develop ArcGIS Server applications with JavaScript, both for traditional web browsers as well as the mobile platform Make your maps informative with intuitive geographic layers, user interface widgets, and more Integrate ArcGIS content into your custom applications and perform analytics with the ArcGIS Online Who This Book Is For If you are a web or mobile application developer, who wants to create GIS applications in your respective platform, this book is ideal for you. You will need Java Script programming experience to get the most out of this book. Although designed as an introductory to intermediate level book, it will also be useful for more advanced developers who are new to the topic of developing applications with ArcGIS Server. What You Will Learn To create an application with the ArcGIS API for JavaScript Build and display a broad range of different geometry types to represent features on the map The best way to leverage a feature layer and display related attribute data The functionality of the wide range of widgets and how to use them effectively Query data to gain new insights into the information it contains Work with tasks to discover and locate features on the map Using the geocoder and associated widgets The ability of the API to provide turn by turn directions and routing capabilities How to use the Geometry Engine and Geometry Service tasks for common geoprocessing operations Integrate content on ArcGIS online and add it to your custom web mapping application In Detail The ArcGIS API for JavaScript enables you to quickly build web and mobile mapping applications that include sophisticated GIS capabilities, yet are easy and intuitive for the user. Aimed at both new and experienced web developers, this practical guide gives you everything you need to get started with the API. After a brief introduction to HTML/CSS/JavaScript, you'll embed maps in a web page, add the tiled, dynamic, and streaming data layers that your users will interact with, and mark up the map with graphics. You will learn how to quickly incorporate a broad range of useful user interface elements and GIS functionality to your application with minimal effort using prebuilt widgets. As the book progresses, you will discover and use the task framework to query layers with spatial and attribute criteria, search for and identify features on the m ...